1988
DOI: 10.1099/0022-1317-69-1-233
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite RNA in Grapevine Fanleaf Virus Strain F13

Abstract: SUMMARYThe F 13 isolate of grapevine fanleaf virus (GFLV) differs from other isolates in that it induces severe symptoms on Chenopodium quinoa. We show here that its particles contain three RNA species with sizes, estimated by electrophoresis in agarose gels containing formaldehyde, of 6800 nucleotides (RNA 1), 3900 nucleotides (RNA2) and 1150 nucleotides (RNA3). The three RNA species are polyadenylated and probably have a genome-linked protein at their 5' end. RNA1 and RNA2 are known to be genomic RNAs. Evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 25 publications
4
68
0
1
Order By: Relevance
“…RNA 3 contains one open reading frame encoding a highly hydrophilic, basic polypeptide of 341 residues and Mr 37275 (Fuchs et al, 1989). In a wheatgerm translation system, RNA 3 directs the synthesis of a protein (P3) with an apparent Mr of 39K (Pinck et al, 1988). However such a polypeptide has never been observed in infected plants.…”
mentioning
confidence: 99%
“…RNA 3 contains one open reading frame encoding a highly hydrophilic, basic polypeptide of 341 residues and Mr 37275 (Fuchs et al, 1989). In a wheatgerm translation system, RNA 3 directs the synthesis of a protein (P3) with an apparent Mr of 39K (Pinck et al, 1988). However such a polypeptide has never been observed in infected plants.…”
mentioning
confidence: 99%
“…The proteins translated from all transcripts comigrated with the P3 protein synthetised from the natural RNA3 (data not shown) (Pinck et al, 1988). This indicated that the full-length clones of RNA3 were not altered during the cloning and mutagenesis steps.…”
Section: In Vitro Translation Of Rna3 Transcriptsmentioning
confidence: 71%
“…RNA3 belongs to the class of large satellites (Fritsch & Mayo, 1989). It has coding capacity for a protein, P3, of M~ 37K and is translated in wheat germ extracts to produce a species of apparent Mr 39K (Pinck et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral genome is composed of two single-stranded positive polarity linear RNA (?ssRNA) segments with a small virus-genome linked protein (VPg) and poly (A) tail at their 5 0 and 3 0 end, respectively. Both RNA segments contain only one open reading frame (ORF) and codes for a polyprotein, which are processed proteolytically at defined dipeptide cleavage sites by the RNA1-encoded proteinase into functional proteins [23]. RNA1 codes for the proteins involved in virus replication [26] and for the viral proteinase [18].…”
mentioning
confidence: 99%